EFEKTIVITAS PROGRAM RESES DPRD KOTA MEDAN DALAM MENYERAP ASPIRASI MASYARAKAT DI KECAMATAN MEDAN LABUHAN - Ibnu Ubayd Dilla; M. Arif Nasution; Agus Suriadi (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2020)
The Recess is conducted in the areas specified by the Member of Medan City Council. DPRD members came to the community and then the community submitted all complaints. Complaints from the community were heard and received direct response from members of Medan City Council. This study aims to examine the effectiveness of the Medan District Parliament Reses program in Medan Labuhan Subdistrict. The type of research in this study is quantitative type with descriptive approach to describe or explain a problem which the result can be generalized. The sample in this research using Slovin formula with sample amount 100 people. Other indicators to show the success of the recess program in this study are divided into several categories: infrastructure, economy, education, security and order, and availability of employment. The results showed that the majority of respondents benefited from improvements in these areas. The overall indicators in this study were well received and approved by the majority of respondents.